Leg-specific modulation of muscle synergies during Tai Chi heel kick in elite athletes - Mo, Jinsong; Jing, Feiyue (Frontiers in Physiology, 2026)
PurposeThe Tai Chi heel-kick is a slow, high-amplitude single-leg movement that places substantial demands on lower-limb coordination, dynamic balance, and controlled force transfer, and is increasingly incorporated into performance training and rehabilitation programs. This study investigated muscle synergies and activation timing differences between the left and right legs of elite Tai Chi athletes during the heel-kick and explored leg-specific neuromuscular control features by combining synergy analysis with spinal segment statistical parametric mapping (SPM).MethodsTwelve national-level elite Tai Chi athletes were recruited. Surface electromyography (sEMG) signals were collected from key lower-limb muscles, and muscle synergies were extracted using non-negative matrix factorization (NMF). The center of activation (CoA) was calculated using circular statistics, and SPM was applied to examine activation differences across the L2–S2 spinal segments.ResultsFour to five robust muscle synergies were identified for both legs, showing high spatial similarity; however, activation timing differed, with the left-leg synergies peaking earlier and the right-leg synergies delayed. CoA analysis indicated an overall phase advance in the left leg and a phase delay in the right leg. Spinal SPM further revealed inter-limb differences during the mid-to-late phase of the movement (40%–80%), with right-leg activation concentrated in L4–S1 segments, whereas the left leg exhibited a broader distribution.ConclusionDuring the Tai Chi heel-kick, the left and right legs share similar synergy composition but differ in temporal activation patterns and spinal segmental drive, suggesting leg-specific modulation within an overall conserved modular structure. Characterizing these timing asymmetries in highly trained athletes provides a neuromuscular reference for designing Tai Chi–based training drills targeting single-leg control and side-to-side balance, and offers a potential framework for tailoring lower-limb rehabilitation exercises that require coordinated support and kicking functions.